The use of Napier Bones props to enhance learning achievement on Grade 5 Math multiplication - Tri Yuriana; Suwardi Suwardi (Prodi PGMI IAIN Salatiga, 2018)
The research aims to find out the improvement of students achievement in the subject of Mathematics on the aspect of multiplication by using the teaching aid of Napier Bones. This research is conducted on the frame of class action research upon two cycles. The context of the research is at Islamic Elementary School (MI) Ma’arif Dukuh, Salatiga. The population covers 21 of fourth grade students. The method of data population includes documentation, observation, and test. Meanwhile, the data analysis uses percentage formula. This research find out that the teaching aid of Napier Bones improve students achievement on the subject of Mathematics upon the research subjects. The significant of the result can be overviewed from the 85.71% of students that have achieved the standard of minimum completeness. It means that the teaching aid of Napier Bones is significantly proven to improve learning achievement on the aspect of multiplication.